Investigations on double perovskite Pr Ba Co2 O6- as an air Electrode for fuel cell Applications - Bangwal, Ajay Shankar (IIT(BHU), 2022)
Abstract is available in the attachment
This Thesis submitted by Phd. Scholar IIT(BHU), Varanasi & Supervised by Prof. Prabhakar Singh.
Keywords: Investigations; Perovskite; Electrode